Free amino acids in nectar: its composition and variability among bat-pollinated plants - Nelly Rodríguez-Peña; Kathryn E. Stoner; Jorge E. Schondube; Angel Durán-Díaz; Luis Barbo Hernández-Portilla; César Mateo Flores-Ortiz (Revista Mexicana de Biodiversidad)
Regardless of the low concentrations at which amino acids are present in floral nectar of bat-pollinated plants, their role as nectar flavor providers and their influence on bats’ foraging decisions have been recognized. Nevertheless, variation in the free amino acids among bat-pollinated plant species has been less studied. The goal of this study was to analyze the nectar free amino acids and to determine its variability among 8 bat-pollinated plant species from 5 families in a Tropical Dry Forest in Mexico. Nectar collections were made opportunistically depending on plants flowering season. We quantified 17 amino acids by HPLC. All 17 free amino acids were present in nectar from the 8 analyzed plant species. The concentration of 12 amino acids is explained by plant species by 19-58%. Analyses showed that Ceiba grandiflora (Malvaceae) was significantly different in asparagine content when compared to Bahuinia pauletia (Fabaceae) and Ceiba aesculifolia (Malvaceae), and in glutamic acid when compared to Ipomoea ampullacea (Convolvulaceae). We discuss the importance of free amino acids in nectar among plant species and their influence on bat pollination ecology.